NILAI-NILAI PENDIDIKAN ISLAM DALAM TRADISI NYONGKOLAN MASYARAKAT SASAK - Nurul Khatimah; Zahraini Zahraini (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2025)
The Nyongkolan tradition is a traditional ceremony conducted by the Sasak people of Lombok as part of their wedding celebrations. This tradition serves not only as a cultural procession but also embodies Islamic educational values that have a significant impact on shaping the character of the community, particularly in terms of ethics, solidarity, and social responsibility. This study aims to analyse the Islamic educational values embedded in the Nyongkolan tradition and explore its potential as an educational tool for the younger generation. The study adopts a qualitative approach, employing in-depth interviews and participatory observation with the community directly involved in the tradition's implementation. The findings indicate that the Nyongkolan tradition teaches principles such as the importance of maintaining relationships, moral education and etiquette, the value of mutual cooperation, solidarity, Islamic brotherhood, and respect for guests. These values align with Islamic teachings that promote the creation of a harmonious, mutually respectful, and solidarity-filled society.